Preliminary X-ray diffraction analysis of the cytoplasmic N-terminal domain of the Na/HCO(3) cotransporter NBCe1-A - Gill, Harindarpal S. (International Union of Crystallography, 2006)
The N-terminal cytoplasmic domain of the Na(+)-coupled HCO[Image: see text] cotransporter NBCe1-A (NtNBCe1) has been linked with proximal renal tubular acidosis. In a previous purification study of recombinant NtNBCe1, crystal growth at a suboptimal protein concentration (<1 mg ml(−1)) yielded small single diamond-shaped crystals that diffracted poorly. In the present study, by increasing the protein concentration 50-fold, the crystal size was doubled and robustness was also improved. Crystal annealing made the crystals suitable for X-ray diffraction. The crystals either belong to space group P3(1)21 or P3(1) with pseudo P3(1)21 symmetry, with unit-cell parameters a = 51.7, b = 51.7, c = 200.6 Å, α = β = 90, γ = 120°, and diffract X-rays to 3.0 Å resolution. The calculated Matthews number is 1.9 Å(3) Da(−1), with two monomers of molecular weight ∼83 kDa in the asymmetric unit. The molecular- replacement packing solution shows that the molecules form dimers by a domain-swapping mechanism.